Effectiveness of an Oral Health Education Program to Improve Mothers’ Awareness of Natal Teeth: A Randomized Controlled Study (2020)
To evaluate the effectiveness of an oral health talk aided by a video on improving the awareness of mothers about natal teeth in two rural communities in southwest Nigeria. A cluster randomized controlled trial was conducted among 80 mothers in two rural communities in Nigeria, randomized into study and control groups. Baseline information was obtained with a pre-tested interviewer administered questionnaire. The mothers in the study group participated in an oral health education program comprising of a video show on natal teeth in addition to an oral health talk. The control group did not receive any intervention. Post-intervention data was obtained three weeks afterwards. Data collected was analyzed with SPSS using paired t-test, independent t-test and Chi-square test. The sociodemographic characteristics of participants in both groups were similar. The mean knowledge, attitude and practice percentage scores for the study group were 38.9 ± 26.3% (pre-intervention) and 73.6 ± 26.2% (post-intervention); while for the control group, the values were 43.2 ± 31.4% (pre-intervention) and 43.9 ± 32.4% (post intervention). The study group, had a 34% increase in knowledge, attitude and practice percentage score (CI=23.7-45.5; t=6.4; p<0.001), while the control group, had an increase of 0.7% (CI=-0.7- 2.2; t=1.00; p=0.323). An oral health education program comprising of oral health talk and a video about natal teeth improved the awareness of mothers about natal teeth as a normal phenomenon